Academic stress and its clinical implications among college students - Tyagi, Vaishnavi; Arora, Niharika; Saran, Brijesh; Debapriya (International Journal of Research in Medical Sciences, 2025)
Background: Academic stress is increasingly recognized as a major mental health concern among undergraduate students worldwide, often leading to symptoms of depression, anxiety, and impaired general health. However, there is limited research focusing on students in nursing, paramedical, and allied health disciplines in India. This study aimed to assess the prevalence of academic stress and examine its relationship with depression, anxiety, stress, and overall general health among undergraduate students. Methods: A cross-sectional study was conducted with 404 students from nursing, paramedical, and allied health sciences at Santosh medical college and hospital. Academic stress was measured using the academic stress scale (ASS), psychological symptoms were assessed with the depression anxiety stress scale-42 (DASS-42), and general health was screened with the general health questionnaire-12 (GHQ-12). Data were analyzed using descriptive statistics and Pearson’s correlation. Results: A substantial 86.13% of students reported moderate to high academic stress levels. Correspondingly, moderate to extremely severe symptoms were reported by 61.4% for depression, 65.3% for anxiety, and 58.7% for stress. Furthermore, 70.8% of students scored above the clinical cutoff on the GHQ-12, indicating compromised general health. Significant positive correlations were found between academic stress and depression (r=0.75), anxiety (r=0.72), stress (r=0.70), and general health impairment (r=0.68) (p<0.05). Conclusions: Academic stress is prevalent among undergraduate health science students and is strongly associated with poor psychological and general health outcomes. These findings highlight the need for early screening and tailored interventions in academic institutions to mitigate adverse mental health impacts and promote student well-being.